Aerosol Measurement Technique: Demonstration at CO2 Technology Centre Mongstad. (January 2016) - de Cazenove, Thomas; Bouma, Richard H.B.; Goetheer, Earl L.V.; van Os, Peter J.; Hamborg, Espen Steinseth
Abstract: There are two main routes for amine emission. The first one is connected to volatile amine emission. The second route is amine emission via aerosols. Recently, it has been observed that under certain conditions and at specific test locations significant aerosol formation and emission can occur. To distinguish between the two routes for amine emission, a novel methodology has been developed. This methodology is based on the separation of the aerosols from the vapour phase in a controlled isothermal modus. To be able to do this, the design of the probe and the sampling procedure should fit to the operational circumstances and is of crucial importance to guarantee isokinetic sampling. The separation of the aerosols is done via an impactor. Using an impactor, not only the total mass of aerosols can be determined, but also the size distribution. At the end of 2013 and at the beginning of 2014, two aerosol measurement campaigns were performed at CO2 Technology Centre Mongstad, Norway. The measurements indicate that small amounts of aqueous aerosols with a broad aerosol size distribution are present in the flue gas stream from gas turbine operations. The presence of aqueous aerosols does not necessarily imply significant amine emission from the amine process. Analysis of the aqueous aerosols indicates low amine content present in the aerosol fractions, and it seems evident that amines present in the gaseous phase inside the absorber column have not been transferred to the aqueous aerosols and by such the total amine emissions are very low.